Discourse on religions other than Islam in 17th century Malay text : an analysis on Hikayat Seribu Masalah - Nurul Fathiah Mohammad Nadzree (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
This study focuses on the discourse of religions other than Islam in the 17th century Malay Islamic text, the Ḥikayat Seribu Masalah. This Malay text produced during the intense period of Islam in the religion. At this time, many literary writings were produced by scholars. Some of the texts were commissioned by the palace. Others were produced by the scholars themselves to spread Islam to the local people. Later, the contents of Islamic religious texts were no longer focusing only on the basic teachings of Islam. Discourses on religions other than Islam were also made directly and indirectly. Ḥikayat Seribu Masalah is one of the Islamic hikāyat produced to address issues on Islam and religions other than Islam. In order to understand how the discourse took place at that time, this study is analysing the contents of Ḥikayat Seribu Masalah. This is a qualitative study and using the method of textual analysis. The validity of the contents is assessed by comparing with the primary sources in Islam, namely the Qur’ān and the Sunnah. It concludes that Ḥikayat Seribu Masalah has addressed a number of issues related to Islam and religions other than Islam. There are similarities between the narratives portrayed in Ḥikayat Seribu Masalah with the Qur’an and Sunnah. The differences are mostly found in the discussion of scriptures and the story of Moses. It is possible to conclude that discussion on religions other than Islam is rooted in Islamic sources.